A potencialidade do manejo florestal comunitário madeireiro na comunidade Santa Rita de Cássia no Projeto de Assentamento Moju/PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2013)
The Forest Management is an activity that aims to use the resources rationally and based on proper techniques with existing regulations and further divided into categories, including the Family and Community Forest Management (MFCF) which is the management of forest resources timbers and non-timber performed by a community or group of people or by a family group. This action provides a better quality of life for those involved generating income, perpetuity of natural resources in the area. This study aims to analyze the potential of Community Forest Management (MFC) Timber in the community of Santa Rita in Settlement Project Mojú / Boards / Pa. The methodology used was the literature, documentary and descriptive. It was observed that this community has potential for deployment and execution of MFC. According to the data analyzed, it can be seen that there is significant area of activity for deployment, as well as most of the settlers and the settled community find themselves capable of carrying out the MFC. Therefore, the social point of view, strengthening the association and the community are crucial to the effectiveness of the process.
Keywords: Atividade florestal; Br 163; Assentamentos rurais; CNPQ:: CIÊNCIAS EXATAS E DA TERRA